2022
DOI: 10.1002/er.7902
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics model based artificial neural network prediction of flammable vapor clouds formed by liquid hydrogen releases

Abstract: Summary The flammable vapor clouds formed by liquid hydrogen release potentially leads to explosions and serious fires. In this paper, an artificial neural network (ANN) model based on the back propagation algorithm was developed to predict the horizontal and vertical hydrogen diffusion distances (the maximum distance of flammable vapor cloud with a hydrogen volume concentration of 4% to the release source in downwind and height direction). For this purpose, liquid hydrogen releases were modeled using a comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Therefore, this study involves a two-phase flow problem, where the gas phase is a mixture of air and hydrogen, and the liquid phase is liquid hydrogen, for which we use the mixture model. The mass conservation equation and momentum conservation equation [19] are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study involves a two-phase flow problem, where the gas phase is a mixture of air and hydrogen, and the liquid phase is liquid hydrogen, for which we use the mixture model. The mass conservation equation and momentum conservation equation [19] are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…These challenges often involve either the unavailability of extensive experimental data or complexities influenced by various factors. Examples include predicting the size of flammable vapour clouds caused by liquid hydrogen release [24], solving problems related to natural convection and conjugate heat transfer [25], predicting solid particle erosion in the oil and gas industry [26], and enhancing the design of centrifugal pumps [27], etc. Based on these studies, the integrated model has shown promising potential in guiding manufacturing processes, explaining physical rules, and enhancing industrial safety.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure of pipelines of hydrogen supply system exceeds 0.15 MPa. Considering the degradation of seals due to vibration or crash, hydrogen leaks from hydrogen supply system, leading to energy loss or even safety accidents such as fire and explosion 4,5 . So the diagnose of hydrogen leakage is critical to save hydrogen energy and improve the reliability of hydrogen supply system of FCV.…”
Section: Introductionmentioning
confidence: 99%